Phenotypic and genetic parameters of circadian rhythms from core body temperature profiles and their relationships with beef steers’ production efficiency profiles during successive winter feeding periods - Durunna, Obioha; Carroll, Jeffery A.; Dailey, Jeff W.; Damiran, Daalkhaijav; Larson, Kathy A.; Timsit, Edouard; Parsons, Rex; Manafiazar, Ghader; Lardner, Herbert A. (Frontiers in Genetics, 2023)
This 2-yr study evaluated differences in circadian parameters obtained from measures of core body temperatures using telemetric reticulo-rumen and rectal devices during two winter feeding regimes in western Canada. The study also estimated phenotypic relationships and genetic parameters associated with circadian parameters and other production traits in each feeding regime. Each year, 80 weaned steer calves (initial age: 209 ± 11 d; BW: 264 ± 20 kg) from the same cohort were tested over two successive regimes, Fall-Winter (FW) and Winter-Spring (WS) at Lanigan, Saskatchewan, Canada. The steers received forage-based rations in both regimes where the individual feed intake was measured with automatic feeding units. During the trial, the reticulo-rumen (RTMP) and rectal (RCT) temperatures were simultaneously measured every 5 minutes using telemetric devices. These were used to calculate the circadian parameters (MESOR, amplitude, and acrophase/peak time) for both temperature measures. Growth and efficiency performance traits were also determined for all steers. Each steer was assigned into inefficient, neutral, and efficient classes based on the SD of the residual feed intake (RFI), residual gain (RG), and residual intake and gain (RIG) within each year and feeding regime. Higher (P < 0.0003) RTMP and RCT MESORs were observed in the FW compared to the WS regime. While the two test regimes were different (P < 0.05) for the majority of the RTMP or RCT temperature parameters, they did not differ (P > 0.10) with the production efficiency profiles. The heritability estimates were higher in FW (0.78 vs. 0.57) than WS (0.50 vs. 0.43) for the rumen and rectal MESORs, respectively. There were positive genetic correlations between the two regimes for the RTMP (0.69) and RCT (0.35). There was a negative correlation (P < 0.001) between body temperature and ambient temperature. The high heritability estimates and genetic correlations for rumen and rectal temperature parameters demonstrate their potential as beef genetic improvement tools of economic traits associated with the parameters. However, there are limited practical implications of using only the core-body temperature as a proxy for production efficiency traits for beef steers during winter.